Implementation of Law No. 21 of 2001 concerning Special Autonomy for Papua in Gefido Village, Abenaho District, Yalimo Regency, Papua Province - Wandik, Yanora; Polii, Johanis; Ginting, Grenaldo (Research Horizon, 2023)
The presence of Law No. 21 of 2001 is the government's answer to overcoming social inequality in Papua. This law contains special policies based on values which include protection and respect for ethics and morals, basic rights of Indigenous Papuans (OAP), Human Rights, supremacy of law, democracy, pluralism, and equality. population, rights, duties and obligations as citizens where the Papuan people can fight for their rights peacefully, because at that time they must be convinced by all components of Papuan society, especially indigenous Papuans, that Special Autonomy is the most appropriate choice. This research uses a qualitative approach with descriptive research methods. To discuss the problems contained in this research, a normative juridical and empirical juridical approach is used. This research was carried out in Gefido Village, Abenaho District, Yanlimo Regency. The Gefido Village Innovative Program (PIO) can be interpreted as one of the Yalimo district government's efforts to improve the welfare of the Gefido Village community by increasing the capacity of Gefido village in developing plans and implementing Gefido village development which focuses on 3 program targets including entrepreneurial development, increasing human resources, as well as providing gefido village infrastructure. The cooperation carried out by the Yalimo government through experts is basically that Gefido village is a source of economic strength. There is still a lot of hidden potential in Gefido village that needs to be explored together. Abundant natural resources and the number of skilled workers make Gefido village a place for very potential business development. If managed professionally, Gefido village can become the main driver of the economy.